Analysis of Volume Fraction and Fiber Orientation on Tensile Strength and Impact Strength of Cannabis Sativa-Polyester Fiber Composites - Ramadhana Luhur Prabangkara; Ismatova Dilafruz Tuymuratovna; Agus Tugas Sudjianto; Aji Suraji (Asian Journal Science and Engineering, 2022)
The development of composite materials in the engineering field is increasingly being used. This is due to its superior properties compared to conventional materials, such as the ratio between strength and density is quite high, rigid, the manufacturing process is very simple and resistant to corrosion and fatigue loads. The article determines the composition of the volume fraction and orientation of the fibers that have the most optimal tensile strength and impact on Sativa-Polyester Cannabis fibers. In this study, the fiber volume fraction was varied into 10%, 15%, 20% and the orientations were 0o , 30o, 45o, 60o and 90o .The method of making specimens in this study used a hand lay up with the ASTM tensile and impact test standards. The result indicates that the fiber volume fraction of 20% with the fiber orientation of 90o has the highest average tensile strength value of 30.56 MPa, compared to other variations. And the fiber volume fraction of 20% with a fiber orientation of 90o has the highest average value of impact strength, namely 493.6 Joules Keywords: Volume Fraction, Cannabis Sativa Fibers, Fiber Composites